Parallel testing of 241 clinical nasopharyngeal swabs for the detection of SARS-CoV-2 virus on the Cepheid Xpert Xpress SARS-CoV-2 and the Roche cobas SARS-CoV-2 assays - Tham, JWM (Walter de Gruyter GmbH, 2021)
10.1515/cclm-2020-1338